1993
DOI: 10.1128/jb.175.10.3067-3074.1993
|View full text |Cite
|
Sign up to set email alerts
|

Localization and nucleotide sequences of genes mediating site-specific recombination of the SLP1 element in Streptomyces lividans

Abstract: SLP1 is a 17.2-kbp genetic element indigenous to the Streptomyces coelicolor chromosome. During conjugation, SLP1 can undergo excision and subsequent site-specific integration into the chromosomes of recipient cells. We report here the localization, nucleotide sequences, and initial characterization of the genes mediating these recombination events. A region of SLP1 adjacent to the previously identified site of integration, attP, was found to be sufficient to promote site-specific integration of an unrelated S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 44 publications
0
25
0
Order By: Relevance
“…pSUM352 was constructed similarly: pSUM49 is pBR322 (6) Figure 1 summarizes the genetic organization of the segment of SLP1 involved in site-specific recombination. We have shown that the int gene encodes a product necessary for integration and have speculated that the open reading frame orf6l encodes a protein implicated in excision (7). To test directly the roles of orf6l and the int gene in SLP1 excision, we expressed Int and Orf6l both separately and concurrently in S. lividans and monitored excision of a nonreplicating hygromycin resistance (Hygr) plasmid that had been integrated site-specifically at the SLP1 attB site.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…pSUM352 was constructed similarly: pSUM49 is pBR322 (6) Figure 1 summarizes the genetic organization of the segment of SLP1 involved in site-specific recombination. We have shown that the int gene encodes a product necessary for integration and have speculated that the open reading frame orf6l encodes a protein implicated in excision (7). To test directly the roles of orf6l and the int gene in SLP1 excision, we expressed Int and Orf6l both separately and concurrently in S. lividans and monitored excision of a nonreplicating hygromycin resistance (Hygr) plasmid that had been integrated site-specifically at the SLP1 attB site.…”
Section: Methodsmentioning
confidence: 99%
“…lividans as well as the conditions used for Southern blot analysis have been described elsewhere (7). The ( Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For many int genes described, the ORF is immediately preceded by or overlaps an ORF which is defined in most instances as, or speculated to be, the excisionase (xis) gene. Up to now, no ORF sharing similarity with the described Streptomyces excisionase proteins (Boccard et al, 1989;Brasch et al, 1993;Brown et al, 1990Brown et al, , 1994Gabriel et al, 1995) could be detected in the sequence surrounding VWB int.…”
Section: A T T T T C C T a C A G A T C C C G G C C T T C G T A G C mentioning
confidence: 99%
“…(including two plasmids of Saccharopolyspora erythraea, previously classified as Streptomyces erythraeus) most often integrate site-specifically into the host chromosome (Bar-Nir et al, 1992;Boccard et al, 1988;Brasch et al, 1993;Brown et al, 1990Brown et al, , 1994Gabriel et al, 1995;Kendall & Cullum, 1986;Shirai et al, 1991;Sosio et al, 1989). In general, such site-specific integration is catalysed by a sitespecific recombinase.…”
Section: Ajoooo47-ajoooo50mentioning
confidence: 99%